Improved diagnosis of small cervical lymph node metastasis using postvascular phase perfluorobutane CEUS in cancer patients - Naxiang Liu; Zhaoming Zhong; Wenrong Lin; Zhongshi Du; Zhougui Wu; Songsong Wu; Lina Tang (BMC Cancer)
Abstract Background Accurate identification of small metastatic lymph nodes (LNs) remains a significant challenge with conventional ultrasound (US) due to its limitations in sensitivity for smaller LNs. The use of contrast-enhanced ultrasound (CEUS), especially with perfluorobutane in the postvascular phase of CEUS, may improve the diagnosis of metastatic LNs in cancer patients. We sought to investigate the diagnostic accuracy of the postvascular phase of CEUS with perfluorobutane in identifying suspected small cervical LNs in cancer patients. Methods This prospective study enrolled consecutive cancer patients with small cervical LNs suspected to be malignant on US from May 2023 to January 2024. All patients underwent CEUS with perfluorobutane injection, followed by observation during the vascular (6–60 s) and postvascular (10–30 min) phases before biopsy. The reference standard was histological assessment of the LNs through biopsy. The US and CEUS features were analyzed to assess the diagnostic performance of the US, vascular phase-CEUS, and postvascular phase-CEUS features, as well as their association with LN size. Results The final dataset included 229 participants (mean age, 57 years ± 11 [SD] [range, 28–80]; 121 women) with 229 suspected LNs, including 125 metastatic and 104 benign LNs. Hypo-enhancement or no enhancement in the postvascular phase of CEUS show excellent sensitivity (97%) and a high negative predictive value (93%). The area under the receiver operating characteristic (ROC) curve of postvascular phase-CEUS is 0.763, significantly higher than that for US (0.574; P < 0.001). Compared to US and vascular phase-CEUS, postvascular phase-CEUS demonstrates superior sensitivity (P = 0.022, and < 0.001, respectively) and accuracy (P < 0.001, all) for diagnosing LNs, irrespective of LN size. Conclusions Postvascular phase-CEUS exhibited excellent diagnostic performance in identifying suspected small LNs in cancer patients. Hyper- or isoenhancing small LNs in the postvascular phase of CEUS were unlikely to be malignant, possibly obviating biopsy.